The dissociation of temporal processing behavior in concussion patients: Stable motor and dynamic perceptual timing. (October 2019) - Bader, Farah; Kochen, William R.; Kraus, Marilyn; Wiener, Martin
Abstract: Temporal processing is an integral aspect of human cognition and perception. Recent studies have suggested that patients suffering from concussion exhibit a deficit in temporal processing, characterized by poor performance on a variety of timing tasks. However, the majority of studies focusing on temporal processing deficits in concussion have focused on visual timing mechanisms. As temporal processing may be dominant for auditory-based processing, and so less susceptible to noise, we investigated patients with TBI and compared them to normal healthy controls on a battery of temporal processing tasks, including paced finger tapping and temporal bisection with sub-second intervals. The results of our investigation found that traumatic brain patients were unimpaired on the paced finger tapping task, suggesting that temporal processing deficits do not extend into motor timing and rhythmicity domain. In the temporal bisection task, TBI patients maintained precision but had a significantly higher bisection point, characterized by a greater propensity to judge stimuli as "short" and were significantly slower than controls. Analysis with a drift-diffusion model of perceptual decision-making revealed that TBI patients were specifically impaired in evidence accumulation, suggesting a smaller signal to noise ratio. Specifically, it demonstrated that patients had higher decision threshold and slower drift rates for accumulating evidence in order to arrive at a decision. Patients had to surmount higher evidence thresholds to reach a decision and were slower than controls in their rate of evidence accumulation. These results suggest specific deficits in temporal perceptual decision-making may predict the neural temporal pathways that may be compromised or unaffected, paving the way for designing targeted therapies to address these impairments.